Organic Matter Removal in a Membrane-Aerated Biofilm Reactor - Da Silva, Tatiana Santos [UNESP]; Matsumoto, Tsunao [UNESP]; Dos Anjos, Mariane Luz [UNESP]; Albertin, Liliane Lazzari [UNESP] (American Society of Civil Engineers (ASCE), 2018)
The control of biofilm thickness is one of the challenges of using the membrane aerated biofilm reactor (MABR) because high thicknesses block oxygen and substrates transferred to the biofilm layers, resulting in MABR performance decay. This research used two recirculation flow velocities for biofilm thickness control: 0.025 m/s in the first experiment and 0.065 m/s in the second experiment, and activity was evaluated through the chemical oxygen demand (COD) removal rate. In the MABR operated in sequential batches using raw domestic sewage, COD removal efficiencies of 56 and 83% were reached for the first and second recirculation velocities, with COD concentration in influent and effluent of 440 and 190 mg/L in the first experiment and 420 and 70 mg/L in the second experiment, respectively. Thus, the variation of the recirculation velocity was shown as an option for biofilm thickness control in MABR.
Keywords: Biofilm; Biological treatment; Membrane; Recirculation velocity